2011
DOI: 10.1007/s10344-011-0596-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-release spatial and social behaviour of translocated male Alpine ibexes (Capra ibex ibex) in the eastern Italian Alps

Abstract: In this 3 years study (2006–2009), we described the\ud space-use and social patterns exhibited by a group of adult\ud male Alpine ibex relocated into the colony of the Marmolada\ud massif (eastern Italian Alps). Our aim was to analyse the postrelease\ud behaviour of translocated Alpine ibexes in comparison\ud with resident males, in order to test the short-term success of\ud the restocking, provide some insight on the duration of the\ud adaptation process and furnish some indications for future\ud restocking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…However, these increased movements did not result in higher emigration rates by translocated tortoises because rates of site fidelity were similar between treatments, and all telemetered translocated tortoises present at the end of the study were within the intended release area. Greater post‐release movements of translocated individuals compared to residents are common in wildlife translocation studies (Hester et al , Nussear et al , Scillitani et al ). These movements are likely due to disorientation, attempts to return to the donor site, or searches for suitable habitat or familiar environmental cues (Stamps and Swaisgood , Dickens et al , Bennett et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these increased movements did not result in higher emigration rates by translocated tortoises because rates of site fidelity were similar between treatments, and all telemetered translocated tortoises present at the end of the study were within the intended release area. Greater post‐release movements of translocated individuals compared to residents are common in wildlife translocation studies (Hester et al , Nussear et al , Scillitani et al ). These movements are likely due to disorientation, attempts to return to the donor site, or searches for suitable habitat or familiar environmental cues (Stamps and Swaisgood , Dickens et al , Bennett et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Translocated tortoises would have had to dispersed only 250 m from the enclosure to achieve a density of 0.81 per ha, which is similar to the mean density reported for several sites across southern Georgia (0.75 per ha; Smith et al ); yet, our median displacement distance was 652 m. Tuberville et al () used enclosure densities of 12–13 per ha but observed the greatest movement distances with unenclosed tortoises. Using high tortoise densities within pre‐release enclosures actually may be beneficial because social interactions among translocated individuals (Tuberville et al ) may enhance population integration (Scillitani et al , ; Bennett et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Largescale movements by translocated caribou may be, in part, due to their inexperience with the landscape or an attempt to reach their native home range (Stamps and Swaisgood 2007;Scillitani et al 2013). Translocated Alpine ibex (Capra ibex ibex) had larger home range sizes than residents until 1 to 2 years post-translocation (Scillitani et al 2012). Similarly, elk translocated from Alberta to Ontario dispersed 20-140 km from the release site (Rosatte et al 2007).…”
Section: Seasonalitymentioning
confidence: 99%
“…Translocation, which is used to establish, re-establish, augment, or mitigate populations in decline, has yielded varied results across a broad range of taxa. Translocations have been used with fishes (Sheller et al 2006, Vincenzi et al 2012, birds (Reynolds et al 2012, White et al 2012, mammals (Van Houtan et al 2009, Scillitani et al 2012, Shier and Swaisgood 2012, and herpetofauna (Nelson et al 2002, Nussear et al 2012. For reptiles and amphibians, translocations have had limited success for some species, with survival rates of translocated animals ranging from 14% to 42% (Griffith et al 1989, Dodd and Seigel 1991, Fischer and Lindenmayer 2000, Germano and Bishop 2009.…”
mentioning
confidence: 99%